PERAN BRAND IMAGE MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP REPEAT PURCHASE - Uttari, Ni Luh Widya; Giantari, I Gusti Ayu Ketut (Buletin Studi Ekonomi, 2022)
The purpose of this study was to explain the role of brand image in mediating the influence of social media marketing on repeat purchases of Mie Gacoan customers in Denpasar City. The sample used in this study was 130 respondents using a questionnaire with google form. The method of determining the sample using purposive sampling method with PLS-based SEM analysis technique. The results show that, social media marketing has a positive and significant effect on repeat purchases, social media marketing has a positive and significant effect on brand image, brand image has a positive and significant effect on repeat purchases, brand image is significantly positive and significant is able to mediate the influence of social media marketing on repeat purchases. Based on the results of this study, Mie Gacoan in Denpasar City has done social media marketing well, so that it has a good brand image to increase repeat purchases.